2009
DOI: 10.5194/acp-9-3825-2009
|View full text |Cite
|
Sign up to set email alerts
|

Regional CO pollution and export in China simulated by the high-resolution nested-grid GEOS-Chem model

Abstract: Abstract. An updated version of the nested-grid GEOSChem model is developed allowing for higher horizontal (0.5 • ×0.667 • ) resolution as compared to global models. CO transport over a heavily polluted region, the Beijing-TianjinHebei (BTH) city cluster in China, and the pattern of outflow from East China in summertime are investigated. Comparison of the nested-grid with global models indicates that the fine-resolution nested-grid model is capable of resolving individual cities with high associated emission i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
152
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(157 citation statements)
references
References 25 publications
5
152
0
Order By: Relevance
“…The 0.5 • × 0.667 • resolution generally provides better results (compared with the observations) than the 2 • × 2.5 • resolution does. This is expected because the finer resolution allows for better resolved topography, meteorological fields, transport and emissions, and therefore provides better agreement with observations, as shown in previous modeling studies (e.g., Zhang et al, 2012;Chen et al, 2009;Wang et al, 2004). The surface BC simulations at 0.5 • × 0.667 • with the a priori emissions show better agreement with the observations compared with those at 2 • × 2.5 • , as evident in both a lower (by 44 % on average, Fig.…”
Section: Sensitivity To Model Resolutionsupporting
confidence: 54%
See 1 more Smart Citation
“…The 0.5 • × 0.667 • resolution generally provides better results (compared with the observations) than the 2 • × 2.5 • resolution does. This is expected because the finer resolution allows for better resolved topography, meteorological fields, transport and emissions, and therefore provides better agreement with observations, as shown in previous modeling studies (e.g., Zhang et al, 2012;Chen et al, 2009;Wang et al, 2004). The surface BC simulations at 0.5 • × 0.667 • with the a priori emissions show better agreement with the observations compared with those at 2 • × 2.5 • , as evident in both a lower (by 44 % on average, Fig.…”
Section: Sensitivity To Model Resolutionsupporting
confidence: 54%
“…Wang et al (2004) reported the first nested-grid GEOS-Chem simulations of carbon monoxide over North America. Chen et al (2009) provided a detailed description of the one-way nesting in the model.…”
Section: Model Description and Simulationsmentioning
confidence: 99%
“…The GEOS-Chem model is driven by assimilated meteorological data from the Goddard Earth Observation System (GEOS-5) of the NASA Global Modeling and Assimilation Office (GMAO) for the year 2006 with a temporal resolution of 6 h (3 h for surface variables and mixing depths). The nested version of GEOS-Chem for Asia (70 E-150 E, 11 S-55 N) uses the native resolution of GEOS-5 meteorological fields at 0.5 Â 0.67 [Chen et al, 2009]. The lowest model layer thickness is~130 m. A global simulation at 2 Â 2.5 spatial resolution is used to provide the boundary conditions every 3 h for the nested domain.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Wang et al, 2004;Chen et al, 2009) and the MOPITT surface-level retrievals to better quantify North American emissions of CO. We focus on the period June 2004 to May 2005 for consistency with and Kopacz et al (2010). As mentioned above, regional inversion analyses are sensitive to the lateral boundary conditions, but use of global models to provide these boundary conditions is problematic if there are biases in transport and the chemistry in the models.…”
Section: Z Jiang Et Al: Regional Data Assimilation Of Multi-spectramentioning
confidence: 99%
“…The nested capability was first implemented in GEOSChem by Wang et al (2004) for the GEOS-3 version of the meteorological fields. The model was then updated by Chen et al (2009) to support the GEOS-5 meteorological fields, with 0.5 • × 0.667 • resolution, which are used here. In the nested simulation the boundary conditions are based on fields archived from a global simulation (at 4 • × 5 • or 2 • × 2.5 • ) with a 3-hour temporal resolution, which are used to rewrite the tracer concentrations in a buffer zone around the nested domain before every transport step.…”
Section: Geos-chemmentioning
confidence: 99%